Development of miniaturized tapered fiber optics diamine oxidase-based sensor for histamine detection - Usman, Hamza Boko (2015)
Estimating the level of histamine in fish and fish products is very important because of their implication in fish poisoning in human; hence, ascertaining histamine levels in the afore-mentioned serves as a chemical index for spoilage. Factors such as expensive instrumentation, time consumption, size and weight are some of the problems with conventional analytical methods of detection. Tapered fiber optics-enzyme based sensors are prospective candidates towards resolving these quagmires due to their portability and simplicity vis-à-vis currently available detectors. Taking into cognizance immobilization as the backbone of any biosensor, this work, reports a technique to immobilize an ordered multilayer of diamine oxidase (DAO) by means of chemical cross-linking on the biconical tapered fiber surface step-wisely alternating between chitosan, glutaraldehyde (GA) and the enzyme. The optimum parameters for the fabricated biosensor included 160 mg/ml DAO, 0.5% chitosan, 2.5% GA, pH 7.0,and tapered fiber surface of waist diameter 12 μm and length 20 mm. A spectrophotometric signal resulted from horseradish peroxidase catalyzed reduction of H2O2, a secondary product of the oxidative deamination of histamine monitored at 450 nm in 0.1 M phosphate buffer (pH 7.0 and room temperature). Atomic force microscopy (AFM), scanning electron microscope (SEM) and spectrophotometric technique confirmed the functionality of the biosensor. The biosensor showed a response and recovery time of 14 sec, a linear response range up to 1.5 mM, a good sensitivity of 0.64 mM-1 with detection and quantification limits towards histamine of 0.086 mM (15.8 ppm) and 0.204 mM (37.7 ppm) and a linear response range of 0-1.5 mM. The sensor showed an excellent anti-interferents property towards the common interferents’ agents of <5%, with good recovery performance towards varying concentration of histamine ranging from 95.6 to 103.6% (RSD <5%). It showed operational stability to up to 40 repeated analyses without significant loss of sensitivity. The developed miniaturized biosensor has a good potential for use in quantitative measurement of histamine in seafood.